Power Laws for Heavy-Tailed Distributions: Modeling Allele and Haplotype Diversity for the National Marrow Donor Program - Slater, Noa; Louzoun, Yoram; Gragert, Loren; Maiers, Martin; Chatterjee, Ansu; Albrecht, Mark (PLOS Computational Biology, 2015)
Author Summary The distribution of haplotypes and species tend to be heavy tailed. The heavy tail is expected from theoretical considerations and is observed in most populations. Accurate measures of diversity are difficult to achieve given that a limited number of common haplotypes represent the majority of the population, whereas the major contributor to haplotype diversity comes from unique haplotypes that are “rare” and present in only a fraction of the population. A major issue for unrelated HSCT donor registries is estimating population coverage with respect to servicing the public need. We here use a power-law methodology that accommodates heavy-tails to estimate both the population coverage by ethnicity in the US and the genetic diversity of alleles and haplotypes. For the European American population, which has the deepest sampling amongst ethnicities, we show that registry population coverage is better than 99%, but the diversity of this sample only represents 40% of the unique haplotypes expected to be found in the population. Population coverage for other ethnicities was poorer and ranged down to 92% as was the case for Native Americans that had the worst coverage. We further show that the formalism developed here produces better estimates of the population properties than existing methods.